THE FEATURES OF ARTISTIC FUNCTIONS IN SCIENTIFIC FANTASY (USING THE EXAMPLE OF RAY BRADBURY AND ISAAC ASIMOV’S WORKS) - Elmurodov Yusuf Kenjayevich (Scientific Impulse, 2023)
The article describes the role and functions of fantastic terms used in the works of world famous science fiction writers Ray Bradbury and Isaac Asimov. In it, in a comparative aspect, the Uzbek variants and meanings of English terms are revealed on the example of artistic fragments. The work in this direction is based on the image of innovations and discoveries in science and technology. Science fiction writers have always been ahead of the times in which they lived. Because they anticipate the future; they devote enough space to scientific hypotheses in their work. And these hypotheses come true over time, becoming reality. Hence, the difference between works of art and others is essentially the same. Moreover, the vocabulary of such works is unique.